Desarrollo de un Modelo Guía de Asistencia Técnica para el Instituto Colombiano de Bienestar Familiar - ICBF (2019)
A crucial element for strengthening the skills and competences of a population is extensionism that seeks to extend (propagate or disseminate) knowledge; likewise, it is crucial for the development of innovation; For extensionism to take effect, it must articulately apply its three axes, technical assistance, technology transfer and training. Technical assistance as an axis of extension is of value great to the Instituto Colombiano de Bienestar Familiar (ICBF) "entity of the Colombian state that works for the prevention and comprehensive protection of early childhood, childhood, adolescence and the welfare of families in Colombia, giving special attention to those in conditions of threat, non-compliance or violation of their rights "(ICBF, s.f.), since it allows to strengthen the institutional management in its three levels (national, regional and zonal) and the quality of the provision of the Public Family Welfare Service, however, does not have a regulatory or regulatory framework designed specifically to provide technical assistance in a transversal manner in the Institute and to service operators or agents of the National Family Welfare System. Therefore, this research addresses the development of the technical assistance axis using the Schnarch product development methodology adapted by Vera, Castiblanco, & Cruz (2018) whose application contributes to the development of the technical assistance guidance model for the Instituto Colombiano de Bienestar Familiar in accordance with the requirements of the National Family Welfare System, the ICBF and the Integrated Planning and Management Model specifically the third dimension: Management with values by results and its policy of organizational strengthening and simplification of processes, and the sixth dimension: Management of Knowledge and innovation. The application of the Schnarch methodology was made through three phases, in the first phase the needs of the interested parties involved in the development of technical assistance in the ICBF were identified using the system dynamics methodology by means of which simulates the behavior of the technical assistance in the ICBF and allows identifying the problems that arise during its management and the respective causes. The second, through an analysis of different models of technical assistance (benchmarking), identified the characteristics and specifications that provide better results in the institutional management and the provision of the Public Family Welfare Service. Finally, in the third phase, the concept of a technical assistance model for the ICBF was elaborated and chosen.